A Pengelolaan Hama dan Penyakit Tanaman Sayuran di Pekon Srikaton Kabupaten Pringsewu: – - I Gede, Swibawa; Hasibuan, Rosma; Aeny, Titik Nur; Purnomo, Purnomo (Agriculture Faculty, Universitas Lampung, 2025)
Members of the Sumber Rejeki 2B farmer group in Srikaton Village, Adiluwih District, Pringsewu, are vegetable farmers. Pest and disease problems are a major challenge in vegetable cultivation. Pest and disease control strategies for vegetable crops have not considered their bioecology. Consequently, pest and disease problems are difficult to address. The objectives of this service to society activity are to: 1) increase the knowledge of partner farmers about important pests and diseases of vegetable plants and their bioecology and 2) increase farmers' knowledge about the principles of pest and disease management of vegetable plants. The PKM activity was carried out in Srikaton village, Adiluwih sub-district, Pringsewu district. As partners involved in this service to society were members of the Sumber Rejeki 2B farmer group. Extension and field visits were carried out on August 27, 2024, at the house of the farmer group leader, Mr. Selamet Riyadi. The service to society method applied was indoor extension and field visits. Indoor extension discussed the topic of pests and diseases of vegetable plants and the bioecology of pests and pathogens that cause disease, pesticides and management of plant diseases. Field visits included analysis of vegetable plant agro-ecosystems. After the service to society activity showed results, there was an increase in participants' knowledge regarding pests and diseases of vegetable plants and their bioecology, as well as their management. Participants requested to conduct similar activities regarding chili and vegetable trading and how to raise capital for vegetable cultivation businesses.